Integrated management of flea beetle and thrips on mungbean in coastal habitat - Ullah, MH; Khan, MMH; Latif, MA; Das, GP; Faruq, MO (Jahangirnagar University Journal of Biological Sciences, 2023)
An experiment was conducted to evaluate the effectiveness of five IPM packages in controlling flea beetles and thrips on mungbeans. The results showed that the lowest number of flea beetles (1.67/plot), the highest reduction in flea beetle population the over control (72.17%), the lowest leaf area damaged (3.33%) and the lowest percent reduction in damaged leaf area versus control (72.99%) was recorded from plots treated with Package 2 (Virtako 80WG @ 0.15 g/L water + white sticky trap). The lowest number of thrips populations (1.00/20flowers), the highest reduction in thrips population versus control(85.0%), the lowest number of damaged flowers (2.33/plant), and the highest reduction in infested flowers over control (79.44%)observed in plots treated with Package 1 (Bioneem plus 1% EC at the rate of 1 ml/L water + white sticky trap). There was a negative correlation between the numbers of flea beetles and thrips with total yield. A negative relationship was observed between flea beetle leaf area infestation and total yield, and between thrips flower infestation and total yield from different IPM packages. This study concluded that IPM package 2 was the most effective package for controlling flea beetles and IPM package 1 was good enough for controlling thrips in mungbeans. Jahangirnagar University J. Biol. Sci. 11(1 & 2): 81-91, 2022 (June & December)